The effects of social media on the body satisfaction of adolescent and young adult females - Wallis, Julia (Kansas State University, 2015)
The thin female body-type perpetuated in the media has historically caused decreased body satisfaction in adolescent and young adult females (Dittmar, 2009). Previous studies have examined the impact of these images in traditional media, but few studies have examined images seen in social media. Therefore, this study examined how social media impacts the body satisfaction of adolescent and young adult females through the variables of age, time spent on social media, social comparison behaviors, and appearance-related attitudes. The study utilized a sample of females between the ages of 14 to 25. As a component of this study, age was broken into two groups, creating a younger (14-18) and older (19-25) group. This allowed the researcher to make comparisons between the two age groups in relation to the variables being studied. An online questionnaire was utilized as part of this study and distributed to college professors, high school instructors, high school and college-age students, and via social media platforms such as Facebook, Instagram, and Twitter. A total of 357 female respondents between the ages of 14 and 25 years old participated in the study. Of the 357 participants, 140 (39.2%) were in the age category of 14-18 and 217 (60.8%) were in the age category of 19-25. Results indicated that participants who accessed their social media accounts more times per day were more likely to engage in social comparison behavior to fashion models and celebrities and peers. In addition, the more participants compared themselves with fashion models and celebrities and peers, the higher their appearance-related attitudes, which lowered their body satisfaction. Age was not a significant factor in predicting time spent on social media, participation in social comparison behavior, or appearance-related attitudes. However, among the sample, younger participants were overall more satisfied with their body than older participants. It was determined that on average, participants checked their social media accounts between 5 and 15 times a day and spent three or less hours daily on social media. These findings have important implications for the fashion and cosmetics industries and AT educators. The results indicate that social media has an impact on young women’s body satisfaction.
Keywords: Body dissatisfaction; Social media; Adolescent females; Social comparison; Communication (0459); Marketing (0338); Women's Studies (0453)